Pengembangan Latihan Soal Keterampilan Membaca Pemahaman Bahasa Jerman Untuk Siswa SMA Kelas XI Semester II di Media Gimkit - Widyatno, Fransisca Amaylia; Wahyuningsih, Fahmi (LATERNE, 2024)
Gimkit is an educational game website in the form of a quiz that can be used as an alternative media for learning German. The background of this research is due to low student interest in learning and the limitations of learning media. This research has a problem formulation on how the development process of reading comprehension skills exercises for high school German class XI semester II in Gimkit media. The purpose of this research is to develop a question exercise on reading comprehension skills of high school German class XI semester II in Gimkit media. The research model used in this study is research and development by Borg and Gall’s (1983), which consists of five stages, namely research and information collecting, planning, develop preliminary form of product, preliminary field testing, and main product revision. The material validation obtained a percentage of 97.55%, indicating that these exercise questions are highly suitable to use. Meanwhile, the media validation obtained a percentage of 99%, indicating that the Gimkit media is highly suitable to use as a learning media. Keywords: Development of Questions, Reading Comprehension Skills, Gimkit